Link Between Opaque Cloud Properties and Atmospheric Dynamics in Observations and Simulations of Current Climate in the Tropics, and Impact on Future Predictions. Issue 17 (7th September 2021) - Perpina, Miguel; Noel, Vincent; Chepfer, Helene; Guzman, Rodrigo; Feofilov, Artem G.
Abstract: Using spaceborne lidar observations and reanalyzes (2008–2014), we relate the vertical wind speed at 500 hPa (ω500 ), indicator of atmospheric circulation, to properties of opaque clouds (altitude and cover) and to the Cloud Radiative Effect (CRE) in the Tropics. We confront those observations with simulations by IPSL‐CM6 and CESM1 climate models using early 21st century emissions. Both models overestimate the average opaque cloud cover. IPSL‐CM6 puts high opaque clouds too high (+2 km), especially in ascendance. CESM1 overestimates the intermediate opaque cloud cover and underestimates small and large opaque cloud covers. Both models agree that cloud properties behave differently at wind speed above (strong subsidence) or below (weak subsidence and ascendance) 20 hPa/day. In future climate (2089–2095), variables affected by biases in current climate are affected by notable changes: IPSL‐CM6 puts high opaque clouds even higher (+2 km) while opaque cloud cover above 30% decreases and below 30% increases in CESM1. Both models predict very little change in the average net CRE in the future. We find that predicted changes of cloud properties can be regionally driven by dynamic or thermodynamic changes, depending on the relationship between opaque cloud altitude and ω500 in the model. Overall, most changes are due to thermodynamic changes in the relationship between cloud property and atmospheric dynamics. Plain Language Summary: The largest incertitude on climate predictions comes from our poor understanding of how clouds will react to a warmer climate. A long‐term record of cloud detections by active sensors, such as lidars, will enable measuring the clouds vertical distribution, one of the properties most sensitive to global warming. Here we investigate how two climate models predict the evolution of the vertical distribution of clouds, in relation to the predicted evolution of large‐scale air motions in the Tropics. We discuss the changes predicted by the models in future climate conditions for cloud properties, and how well they simulate them in current climate conditions, compared to current retrievals from satellite sensors. We also find that when models generate upward or downward air motions, they move opaque clouds higher or lower in very different ways. This explains why, even if both models similarly predict that tropical atmospheric circulation will slow down in the future, they predict different changes in cloud altitude. Key Points: We document how both models predict cloud properties in the present and in a future, warmer climate with weakened Walker/Hadley circulation Both models show cloud properties evolve differently with vertical wind speeds smaller or larger than 20 hPa/day Cloud properties that suffer from biases in model simulations of current climate are affected by large changes in the future climate